(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The aim of this work was to assess the biological activity of benzothiazoles, substituted with diverse groups, with respect to their role as antidiabetic compounds. Twenty four new benzothiazole compounds were newly developed, These compounds were tested for their efficacy in alloxan and streptozotocin-induced diabetic rats. Initially, the given compounds underwent computational models via ADMET and Toxicity Prediction models for testing oral bioavailability and toxicity. As recommended by ADME prediction profiles, chosen compounds were subjected to in vivo experiments at 350 mg/kg body weight. Several derivatives exhibited substantial blood glucose lowering activity as compared to the diabetic control group of animals and among those derivatives, compounds 6f and 7d were found to possess more potent antidiabetic activity similar to that of glibenclamide. Similarly, subsequent research on diabetic rats provoked by streptozotocin also revealed the efficacy of compounds 6e, 6f, 6i, 7d and 7f to control diabetes. The findings here presented reveal that the title substituted benzothiazoles, especially compound 6f and 7d have the potential to be considered as future antidiabetic drugs. To search the real potential therapeutic application of these compounds in the management of diabetes, there is need for further research on the efficacy and safety of these compounds.